Dakwah dalam Masyarakat Multikultural; Perjuangan antara Identitas, Pluralitas, dan Puritanitas: Kajian Empiris Masjid Cheng Hoo Makassar, Sulawesi Selatan - Suharti; Erwin Jusuf Thaib; Arfan Nusi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This article focuses on research on the role of the Cheng Hoo Mosque in the multicultural da'wah movement in Makassar City and the challenges it faces. This study uses a qualitative method with a sociological and da'wah approach. The purpose of this paper is to analyze the existence of multicultural da'wah at the Cheng Hoo Mosque in Makassar City and the challenges it faces from aspects of identity, plurality, and puritanity. Data were collected through interviews, field observations, and documentation studies. The research findings show that the Cheng Hoo Mosque is a religious and cultural identity of the Chinese Muslim community in Makassar City. The challenge faced by multicultural da'wah is plurality, especially in the field of religion and religious puritanism which leads to division. The multicultural da'wah movement at Cheng Hoo Mosque is carried out with three approaches, namely non-mazhab mosques, mosques that are open to all groups, across cultures and religions, and acceptance and respect for local culture. Key words: Cheng Hoo Mosque, da’wah, multicultural